1978
DOI: 10.1530/jrf.0.0540021
|View full text |Cite
|
Sign up to set email alerts
|

Luteal function in sows after unilateral infusion of PGF-2  into the anterior uterine vein on different days of the oestrous cycle

Abstract: Prostaglandin F-2alpha (1.5 mg over 10 h) was infused into the anterior uterine vein of pigs on Days 6, 8, 10, 12, 14 and 15 of the oestrous cycle. At each stage of the cycle PGF-2alpha suppressed luteal function although the fall in progesterone secretion was much greater and statistically significant when the infusion was performed on Days 12, 14 and 15 of the cycle than on Days 6, 8 and 10. The concentrations of cAMP was depressed on Days 15 and 17 and fatty degeneration of luteal cells on Days 6--8 or 14 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1979
1979
2004
2004

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 16 publications
(26 reference statements)
1
8
0
Order By: Relevance
“…In the cyclic sows with elevated progesterone before PGF2, treatment, no decline in ovarian venous progesterone was observed within 90 min after administration of PGF,,. This is in agreement with other studies in the cyclic pig that indicate that it takes at least 4-6 hr before a decline in progesterone occurs in response to a PGF,, challenge via the utero-ovarian vein (10,22). Thus, although progesterone levels could not be used as an indicator of the acute effects of a bolus dose of PGF2U, they were useful as an indicator of the functional status of the corpus luteum before prostaglandin treatment.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the cyclic sows with elevated progesterone before PGF2, treatment, no decline in ovarian venous progesterone was observed within 90 min after administration of PGF,,. This is in agreement with other studies in the cyclic pig that indicate that it takes at least 4-6 hr before a decline in progesterone occurs in response to a PGF,, challenge via the utero-ovarian vein (10,22). Thus, although progesterone levels could not be used as an indicator of the acute effects of a bolus dose of PGF2U, they were useful as an indicator of the functional status of the corpus luteum before prostaglandin treatment.…”
Section: Discussionsupporting
confidence: 91%
“…When no effect of 10 pg of PGF2, on RLX release was observed, a 10fold higher concentration ( 100 pg) was tested in both pregnant and cyclic sows. Blood samples (3 ml) were taken over a 10-sec period by aspiration from the venous cannula at intervals before infusion ( 5 and 2 min) and at 0, 2, 4, 6,8,10,15,20,25,30,40,50,60,75, and 90 min after infusion. Total blood volume obtained over the sampling period was approximately 5 1 ml.…”
Section: Methodsmentioning
confidence: 99%
“…In the nonpregnant pig, the life span of the CL is 16-18 days [2], and at the end of this period the CL undergoes luteolysis as a result of secretion of prostaglandin F 2␣ (PGF 2␣ ) by the uterus [3]. The pig is rather unique among the livestock species in that its CL display an extended period of refractoriness to the luteolytic effects of exogenous PGF 2␣ , which lasts approximately 12 days [4]. However, this insensitivity can be overcome by repeated administration of PGF 2␣ on Days 5-10 following the onset of estrus, successfully reducing the mean inter-estrus period from 19.8 Ϯ 0.6 to 13.3 Ϯ 0.5 days and inducing premature CL regression [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In pigs, however bilateral regression occurs after semihysterectomy (Spies, Zimmerman, Self & Casida, 1958), although if as little as one-quarter of one horn is left intact, the corpora lutea on the opposite side do not regress (du Mesnil du Buisson, 1961). Krzymowski, Kotwica, Okrasa, Doboszynska & Zieçik (1978) reported that when pro¬ staglandin (PG) F-2a was infused into the anterior uterine vein the corpora lutea in the contralateral ovary also regressed. The corpora lutea in the opposite ovary contained smaller amounts of cAMP and histologically appeared to show more fatty degeneration than did the control ovaries.…”
Section: Introductionmentioning
confidence: 99%